ANALISIS KEPATUHAN WAJIB PAJAK ORANG PRIBADI DENGAN KEBIJAKAN SUNSET POLICY DAN TAX AMNESTY - Yuni Rachmawati; Yuanty Aprilia Widy (Universitas Tridinanti, 2019)
ABSTRACT Sunset policy and tax amnesty are efforts made by the tax authorities to provide opportunities for taxpayers who have been disobedient to report their assets and income honestly. These two policies are carried out as an effort to increase the taxpayers' willingness to pay so that tax optimization can be achieved. The purpose of this study was to determine the compliance of taxpayers after the implementation of the sunset policy and tax amnesty. The author uses observation, interview and documentation techniques. The results showed that taxpayer compliance increased by 50% through the tax amnesty Volume III (2017) while taxpayer compliance through Sunset Policy volume II was only 42.9% (2015).Keywords: Sunset Policy, Tax Amnesty, and Tax Compliance